Evaluating the Efficacy and Safety of Alpha-Hydroxy Acids in Dermatological Practice: A Comprehensive Clinical and Legal Review - Almeman AA (Dove Medical Press, 2024)
Ahmad Abdulrahman Almeman Department of Pharmacology, College of Medicine, Qassim University, Burydah, Qassim, Saudi ArabiaCorrespondence: Ahmad Abdulrahman Almeman, Department of Pharmacology, College of Medicine, P.O.Box 6688, Burydah, Al-mulaida, Qassim, Saudi Arabia, Email meman@qu.edu.sa; ahmadalmeman@gmail.comAbstract: The global market for alpha-hydroxy acids (AHAs) is undergoing significant expansion, propelled by increasing demand for skincare products that address aging and environmental damage. This review focuses on the dermatological applications of AHAs, particularly in cosmetic formulations like chemical peels. We have identified that AHAs, such as glycolic and lactic acids, enhance skin rejuvenation by promoting apoptosis in skin cells, boosting collagen and elastin synthesis, and improving skin texture and luminosity. Our comprehensive analysis reveals a nuanced understanding of AHAs' effectiveness across various skin types and conditions, demonstrating their broad utility in treating conditions like acne, hyperpigmentation, and photoaging. However, the optimal concentrations for therapeutic efficacy with minimal side effects are yet to be precisely defined, necessitating further research. Regulatory compliance is underscored as essential for the safe application of AHAs in cosmetics, with international guidelines recommending specific concentrations and pH levels to minimize potential skin irritation. In Conclusion, the review highlights the effectiveness of AHAs in cosmetic dermatology, emphasizing the necessity for continued research and rigorous regulatory adherence to maximize their safe and beneficial application worldwide.Keywords: chemical peels, alpha hydroxy acids, practice guidelines, glycolic acid